Only for the brave at heart: essays rethinking race, crime, and justice - Pettiway, Leon E. (Meishin, 2023)
"Only when we transform our minds can we break the chains of our mental enslavement and find true liberation. Only For the Brave at Heart: Essays Rethinking Race, Crime, and Justice attempts to create an intellectual movement that reimagines how we might think about the intersectionality of race, crime, and the administration of justice."--Page [4] of cover